Endoscopic Pancreas Fluid Collection: Methods and Relevance for Clinical Care and Translational Science. (September 2016) - Hart, Phil A; Topazian, Mark; Raimondo, Massimo; Cruz‐Monserrate, Zobeida; Fisher, William E; Lesinski, Gregory B; Steen, Hanno; Conwell, Darwin L
Abstract : N/A: Pancreatic secretions have an important role in the regulation of a normal nutritional state but can be altered owing to a variety of pathophysiological mechanisms in the context of exocrine pancreatic disease. The development of an endoscopic technique for collection of pancreatic fluid, termed endoscopic pancreatic function testing, has led to improved understanding of these alterations and is particularly helpful to characterize chronic pancreatitis. In addition, investigators have found endoscopically collected pancreatic fluid to be a valuable biofluid for the purposes of translational science. Techniques such as proteomic, cytokine, genetic mutation, DNA methylation, and microRNA analyses, among others, can be utilized to gain a better understanding of the molecular characteristics of chronic pancreatitis and other pancreatic diseases. Endoscopic collection of pancreatic fluid is safe and relatively straightforward, permitting opportunities for longitudinal analysis of these translational markers throughout the course of disease. This manuscript summarizes our current knowledge of pancreatic fluid, with an emphasis on proper techniques for sample collection and handling, its clinical utility, and preliminary observations in translational science.